From Renaissance To Robot: Paradigm Shifts In Visual Art - Mokhtar , Mumtaz; Wan Mohd Daud , Wan Samiati Adriana; Mudzafar, Nabilah (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This paper investigates the paradigm shifts in art from the Renaissance to the contemporary digital age, emphasizing how technological innovation has redefined the value, function, and perception of art. During the Renaissance, art embodied humanistic ideals and served as a medium of communication between the artist and the audience through form, symbolism, and mastery of technique. In contrast, the advent of machines, robotics, and artificial intelligence has transformed the processes of creation, authorship, and aesthetic judgment. These developments challenge traditional notions of artistic authenticity and raise questions about the evolving relationship between human creativity and algorithmic generation. By tracing the historical continuum from the Renaissance’s pursuit of perfection to the AI era’s pursuit of simulation and automation, this study critically examines how the meaning and worth of art have been renegotiated. It concludes by calling for a re-examination of art education to sustain authenticity and critical engagement in an age where human and machine creativity increasingly intersect.